The Gargasian (Middle Aptian) strata from Cassis-La Bédoule (Lower Aptian historical stratotype, SE France): planktonic and benthic foraminiferal assemblages and biostratigraphy - Moullade, Michel; Tronchetti, Guy; Bellier, Jean-Pierre (HAL CCSD, 2005)
International audience This paper presents a thorough analysis of foraminiferal assemblages ranging in age from the Bedoulian-Gargasian transition to the middle Gargasian in the Cassis-La Bédoule area (SE France), the historical stratotype of the Lower Aptian substage. This region is particularly suitable for detailed studies of Aptian foraminifera owing to rapid and continuous sediment depositional rates and well- diversified microfaunas. The ranges of benthic forms appear to be fairly stable but some species (Praedorothia praeoxycona, Lenticulina cf. nodosa, Astacolus crepidularis, Globorotalites bartensteini) become extinct at the end of the Bedoulian and thus can be used to separate this substage from the Gargasian. The stratotypic area also offers an opportunity to follow the evolution of planktonic forms step by step at a crucial period of their history, when modalities of speciation and phylogenetic relationships appear to be particularly complex. The important morphologic variability of Aptian planktonic foraminifera does not help finding stable stratigraphic markers; nevertheless, we are able to propose a biozonation comprising five zones (Cabri, Luterbacheri, Ferreolensis, Barri, Algerianus) for the interval under consideration, usually subdivided into three zones. Our study of foraminiferal assemblages and species took into account the range of variability among populations and not just the characteristics of a single specimen, such as the holotype. As a result this paper provides new taxonomic precisions on certain planktonic species hitherto controversial or possibly of doubtful validity. ––– Le Gargasien (Aptien moyen) de Cassis-La Bédoule (stratotype historique de l'Aptien inférieur, SE France) : associations et biostratigraphie des Foraminifères benthiques et planctoniques.- L'analyse approfondie des associations de Foraminifères depuis les termes du passage Bédoulien-Gargasien jusqu'au Gargasien moyen a été réalisée dans le secteur de Cassis-La Bédoule (SE France), stratotype historique du ...